Wireless and Configurationless iClassroom System - UMP, FSKKP (Faculty of Computer Systems and Software Engineering, 2013)
The Wireless and Configurationless iClassroom System is targeted for any level of classroom environment be it in a primary education environment up to tertiary education environment. This is because of its unique zero-configuration environment that allows users of limited technological backgrounds to operate with absolute ease.